Correction: Solvent-controlled synthesis of multicolor photoluminescent carbon dots for bioimaging. Issue 46 (23rd August 2019) - Yan, Yang; Xia, Longyu; Ma, Lan
Abstract : Correction for 'Solvent-controlled synthesis of multicolor photoluminescent carbon dots for bioimaging' by Yang Yan et al., RSC Adv., 2019, 9, 24057–24065.